RESPON PESERTA DIDIK TERHADAP PENYISIPAN NILAI-NILAI AL-QUR'AN PADA PEMBELAJARAN HUKUM ARCHIMEDES - Fimelia Suci Rahmani; Tomo Djudin; Erwina Oktavianty (Universitas Tanjungpura, 2021)
This study aims to determine students’ responses to the insertion of Al-Qur’an values in learning Archimedes law. This research is a survey research. Sampling was taken using the Proposive Sampling method with the whole group technique, namely students of class XI MIA B who had been given learning by inserting Al-Qur’an values in Archimedes law learning into samples in learning. This research instrument was a responses generally agreed with tha insertion of Al-Qur’an values in learning with a percentage of 79,41%. This suggests a very interesting criterion. Based on these findings, the inclusion of Al-Qur’an values in the learning process can be used as an alternative for learning to implement learning.